The Analysis of Visual and Verbal Expressions of FIJI Water Sports Cap Posters - Kevin Jonathan; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Advertisement is made to persuade consumers to purchase a certain product. To have a successful persuasion, advertisers must pay attention to the major components of the advertisement, like verbal and visual expressions. In this paper, we analyze the messages that FIJI Water Sports Cap wants to convey in its posters, and how they are supported by the use of verbal and visual expressions. To reveal the meaning of the posters, we use Chandler’s theory of process of signification and the supporting theory of metaphor. Our findings show that the messages in FIJI Water Sports Cap posters are related to its naturalness and the benefit of consuming it. The messages are produced in the second level of process of signification or the connotation level. The findings also reveal how visual elements of the posters support the messages that FIJI Water Sports Cap wants to convey.